Incidence of grass and weed sensitization in Bangkok, Thailand: a clinical study - Aud-in, Sirirat; Juprasong, Yotin; Pinkaew, Bannapuch; Talek, Kanokporn; Tantilipikorn, Pongsakorn; Songnuan, Wisuwat (Frontiers in Public Health, 2024)
Background Allergic rhinitis (AR) is a prevalent public health concern globally, significantly impacting quality of life. In Thailand, the prevalence of AR is rising, with grass and weed pollen identified as primary outdoor triggers. Objectives This study aimed to (1) assess patterns of pollen sensitization in Thai AR patients and (2) investigate correlations between demographics/clinical data and SPT results. Methods A total of 121 individuals aged ≥18 years with clinically diagnosed AR were recruited. Skin prick testing (SPT) was performed using a panel of commonly encountered tropical grass and weed pollen extracts. SPT wheal sizes and clinical symptom scores were recorded. Correlations between SPT outcomes and symptom scores were analyzed. Results Among the participants, 104 (85.95%) exhibited positive SPT reactions to at least one pollen type. Nutsedge (76/121), para grass (57/121), and Bermuda grass (48/121) were the most frequently identified allergens. Hurricane grass elicited the strongest reaction, evidenced by the highest average wheal size (6.2 mm). Poly-sensitization was observed in 77 (63.6%) of the SPT-positive individuals, with most cases involving two different pollen extracts (35/77). Notably, AR severity positively correlated with both average wheal size and the number of positive SPT tests. Conclusion This study highlights nutsedge, para grass, and Bermuda grass as major allergenic pollen sources for Thai AR patients. Including nutsedge, hurricane grass, and careless weed in clinical SPT panels is recommended for improved diagnostic accuracy. Additionally, the positive correlation between AR severity and pollen reaction strength emphasizes the importance of implementing patient education and avoidance strategies.